Systematic Review of Diagnostic Tests for Vaginal Trichomoniasis. Issue 5 (2000) - Patel, Sangnya R.; Wiese, Wilhelmine; Patel, Sanjay C.; Ohl, Christopher; Byrd, James C.; Estrada, Carlos A.
Abstract : Objective: To review critically and to summarize the evidence of diagnostic tests and culture media for the diagnosis of Trichomonas vaginitis. Methods: We performed a systematic review of literature indexed in MEDLINE of studies that used Trichomonas culture as the reference standard (9, 882 patients, 35 studies). Level I studies (5, 047 patients, 13 studies) fulfilled at least two of three criteria: 1) consecutive patients were evaluated prospectively, 2) decision to culture was not influenced by test results, and 3) there was independent and blind comparison to culture. Results: The sensitivity of the polymerase chain reaction technique (PCR) was 95% (95% CI 91% to 99%), and the specificity was 98% (95% CI 96% to 100%). One study was classified as Level I evidence (52 patients). The sensitivity of the enzyme-linked immunosorbent assay was 82% (95% CI 74% to 90%), and the specificity was 73% (95% CI 35% to 100%). The sensitivity of the direct fluorescence antibody was 85% (95% CI 79% to 90%), and the specificity was 99% (95% CI 98% to 100%). Sensitivities of culture media were 95% for Diamond's, 96% for Hollander, and 95% for CPLM. Conclusions: The sensitivity and specificity of tests to diagnose trichomoniasis vary widely. Infect. Dis. Obstet. Gynecol. 8:248–257, 2000.